"HUMAN INTERESTS ABOVE ALL" IN THE NEW UZBEKISTAN REFLECTION OF IDEAS IN THE POLITICAL LIFE OF SOCIETY - Nabiyev Mansur Jamhur oglu (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Social ideas have a unique contribution to ensuring the democratic development of the new Uzbekistan. In particular, based on the ideas put forward by the President of the Republic of Uzbekistan Shavkat Mirziyoyev, “Human interests are above all else” and “The people should work for the state bodies, not for the state bodies,” great work has been done in our country to ensure human rights from 2017 to the present. This article reveals the social reforms being carried out in our country to ensure human rights with the help of analytical conclusions.